Neutrophil Lymphocyte Ratio (NLR) in COVID-19 Patients Receiving Convalescent Plasma Therapy - Desyani Ariza; Andi Maya Kesrianti; Tazya Anggraini Ruslan (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2022)
Recently, a new RNA virus from the Coronaviridae family was discovered, known as SARS-Cov-2. This virus causes pneumonia and inflammation in the body. One of the laboratory tests used to see inflammation in the body is the Neutrophil Lymphocyte Ratio, or often abbreviated as NLR. NLR is one of the markers of inflammation that can be used simply, efficiently, and reliably because of its high stability and sensitivity. Higher NLR values tend to lead to a severe and poor prognosis, so this test can be done by monitoring patients with confirmed Corona Virus Disease 2019 (COVID-19). The purpose of this study was to determine the neutrophil lymphocyte’s ratio in COVID-19 patients receiving convalescent plasma therapy. This research method is a quantitative observation using a descriptive approach. Quantitative observational research is used to analyze data in the form of numbers from the results of laboratory tests. The results obtained from 17 research subjects, namely the NLR values before convalescent plasma therapy were obtained in as many as 6 patients (35%) with normal NLR values below 3.13 and NLR values are increasing above 3.13 in as many as 11 patients (65%). Meanwhile, after convalescent plasma therapy, there were 8 patients (47%) with normal NLR below 3.13 and NLR values increasing above 3.13 as many as 9 patients (53%). This research concerns about changes in NLR values before and after convalescent plasma therapy, which before convalescent plasma therapy there were 6 patients with normal NLR values and after convalescent plasma therapy increased to 8 patients with normal NLR values which indicate a better good prognosis.